2020
DOI: 10.1002/pssa.202070021
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Hematite Decorated with Gold Nanoparticles for Functionalization and Biocompatibility

Abstract: Biocompatibility Hematite nanowires grown on the surface of microtubes are decorated with gold nanoparticles produced in situ by the use of the reducing capacity of the semiconductor on gold ions. Gold nanoparticles allow functionalization with thiolic compounds and improve the biocompatibility of the materials significantly for cell viability with respiring mitochondria. More details can be found in article number http://doi.wiley.com/10.1002/pssa.201900589 by Lucivaldo R. Menezes, Iseli L. Nantes‐Cardoso, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…XPS spectrum of Au4f presented the typical sharp doublet peaks at 87.78 ± 0.03 eV and 84.08 ± 0.03 eV assigned respectively to Au 4f7/2 and Au 4f5/2 binding energies (BE) of nanoparticulated zero valent Au 0 (87.7 eV and 84.0 eV). [ 55 ]. The decomposition of the O1s XPS spectrum in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…XPS spectrum of Au4f presented the typical sharp doublet peaks at 87.78 ± 0.03 eV and 84.08 ± 0.03 eV assigned respectively to Au 4f7/2 and Au 4f5/2 binding energies (BE) of nanoparticulated zero valent Au 0 (87.7 eV and 84.0 eV). [ 55 ]. The decomposition of the O1s XPS spectrum in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, gold nanoparticles (AuNPs) and carbon dots (CDs) have gained considerable attention due to their tunable optical properties, superior biocompatibility, and amenability to surface modification. 28,29 Indeed, several reports have shown that AuNPs can be utilized for optical detection, nanoenzyme catalysis, and medical treatment (reviewed in ref 23). 30 CDs have also exhibited potential for optical and electrochemical sensing.…”
mentioning
confidence: 99%
“…Recent advancements in nanotechnology have had positive impacts on the bioanalytical and biomedical fields. , For example, nanoparticles can now be used to enhance the physicochemical properties of molecular scaffolds via surface modification and functionalization. Among them, gold nanoparticles (AuNPs) and carbon dots (CDs) have gained considerable attention due to their tunable optical properties, superior biocompatibility, and amenability to surface modification. , Indeed, several reports have shown that AuNPs can be utilized for optical detection, nanoenzyme catalysis, and medical treatment (reviewed in ref ) . CDs have also exhibited potential for optical and electrochemical sensing.…”
mentioning
confidence: 99%